Analysis of Policy Implementation for The Improvement Capability of Internal Government Supervisory Apparatus (APIP) at Inspectorate General of Ministry of Health - Sarjono, Ajeng Hadiati; Sulistiadi, Wachyu (Journal of Indonesian Health Policy and Administration, 2018)
The capability of the Internal Government Supervisory Apparatus (APIP) is the ability to carry out supervisory tasks consisting of three interrelated elements: capacity, authority, and competence. The objective of this research is to give policy recommendations for enhanced APIP capability in the Inspectorate General of the Ministry of Health. This research is a descriptive study with qualitative analysis method with in-depth interview and literature study. Results of this research indicate that there are some obstacles: the socialization done only to some employees of Itjen; no Special Team on the process of improving APIP capability; the time and task division is unclear; has no special budget yet; there has not been a derivative rule from the Internal Audit Charter (IAC); no reward and punishment system; no documentation of supervision working papers; the policy has not been internalized. This research concludes that the implementation of the policy has not been reached optimally based on PERKA BPKP Number PER-1633/K/JF/2011. Communication is the most influential factor in the implementation of APIP enhancement policy. The recommendation from this research are consistently socialize to employees within the Inspectorate General, make Standard Operating Procedures (SOP), allocate budget activities in 2018, create memorandum of understanding with other agencies, and self assessment and program evaluation absolutely must do continuously.